Monitoring approach for online security of cryptographic protocol - Yu-na ZHU; Ji-hong HAN; Lin YUAN; Yu-dan FAN; Han-tuo CHEN; Wen GU (Tongxin xuebao)
Previous methods can not detect the low-interaction attacks of protocol logic.A cryptographic protocol online monitoring approach named CPOMA was presented.An ontology framework of cryptographic protocol features was constructed for the unified description of cryptographic protocol features with different types.Based on the framework,a feature weighting method was proposed by fuzzy subspace clustering first,and the individualized feature database of cryptographic protocols was built.On this basis,a self-learning method was presented for protocol identification and session rebuilding,and then abnormal protocol sessions were detected online.Experimental results show that CPOMA can identify protocols,rebuild sessions,detect abnormal sessions efficiently,and can improve the online security of cryptographic protocols.